Analysis and Design of Architecture Enterprise at PT. PLN. Enjiniring - Sutejo, Lukas Bagus; Chernovita, Hanna Prillysca (Sistemasi: Jurnal Sistem Informasi, 2023)
In the industrial era 4.0, as it is now, all-digital processes to support business are commonplace. So that we need a design that can align between the business processes of a company with the information system owned by the company. PT. PLN (Prima Layanan Nasipnal) Enjiniring is a company engaged in the field of electricity engineering consulting under the auspices of or a subsidiary of PT. Perusahaan Listrik Negara (Persero), which carries out planning, construction, operation and maintenance as well as performance management in electricity and non-electricity infrastructure and the role of Information Technology is very necessary in the running of Business Processes in this company. The application of Information Systems and Information Technology at PLN. Enjiniring is currently not yet integrated with each other so that the application of IS/IT has not run optimally and has not been effective in data exchange, so it is necessary to hold integration of information systems managed by the Information Technology Section of PT. PLN. Enjiniring so that in to design an integrated information system requires Enterprise Architecture (EA) using the TOGAF ADM framework. The results of this EA design are in the form of artifacts in the TOGAF ADM component which are expected with these artifacts to become recommendations in the implementation of integrated information system infrastructure in information systems managed by the Information Technology Section of PT. PLN. Enjiniring so that with the implementation of an integrated information system it can support the process business that runs on PT. PLN. Enjiniring.